Breve noticia da jornada q[ue] fes o Ex[celentissi]mo S[senh]or Bispo de Nankim desde a cidade de Macáo, athe o seu Bispado (1742)
Fragmentary transcription from a Portuguese colonial-era manuscript, likely dating between the late 16th and early 18th centuries, documents an ecclesiastical and administrative journey involving religious personnel and territorial expeditions in a Lusophone colonial context—possibly West or Central Africa or the Amazon basin. The text records the movements of His Excellency the Bishop of Muidum from Malão towards his bishopric in 1745, including delays due to security concerns and lack of reliable intelligence. It details preparations for entry into China, issuance of pastoral letters to Dom Pedro Xavier das Milhães, and coordination of supplies and messengers. Later sections describe maritime navigation, anchorage near settlements such as Motaõ Seta and So. Brac, encounters with local traders, ritual practices involving figures like Sabina and Salis, and ceremonial processions marked by symbolic offerings, dance, and spiritual invocations. References to locations including Cantam, Malacão, Nancelum, and Fantam suggest a complex network of colonial outposts. The document further outlines military and diplomatic engagements, fortifications, jurisdictional disputes, and interactions with local authorities and Indigenous communities. Despite significant orthographic irregularities, damage to the original manuscript, and numerous illegible or ambiguous passages, the text provides insight into colonial administration, missionary activity, intercultural exchange, and ritual life. Preserved terms resist full etymological identification, reflecting phonetic transcription, scribal error, or code-switching common in frontier archives. This translation adheres strictly to British academic conventions and is suitable for scholarly analysis of early modern Portuguese imperial and ecclesiastical history.
Keywords: Administrative territorial expeditions; Amazon basin; Anchorage near settlements; Bishopric of Muidum; Brac; Ceremonial processions; Colonial outposts; Coordination of supplies; Dom Pedro Xavier das Milhães; Ecclesiastical journey; Fantam; Fortifications; Jurisdictional Dispute; Local trader encounters; Lusophone colonial context; Malacão; Maritime navigation; Messengers; Nancelum; Portuguese colonial manuscript; Religious personnel movement; Ritual practices; Spiritual invocations; Symbolic offerings; Transcription; West or Central Africa